Socialisation as an internal potential self-development way of a VET school student's personality - Vovkovinskyi, Mykola (Professional Pedagogics, 2015)
Socialization is the process of individual‘s entering in a social system, his integration and interaction with society. However, sometimes socialization is replaced by the concept of «adaptation», that is through the prism of the concept of «adaptation» socialization is seen as the process of person‘s entering in the social environment and his adaptation to cultural (norms, attitudes, value models, ideas which are the factors that shape the behavior of the individual as well as products of such behavior), psychological (are passed within the scales of relevant community through social contact and dependent on the system interpersonal relations) and sociological (social: housing, educational institutions, objects of nutrition, medicine, security, infrastructure, environmental) factors. As we can see, there is no clear distinction between basic and higher spiritual needs of personality.Using pyramid by A. Maslow we have concluded that socialization involves first satisfying adaptation needs of a person (physiological: hunger, thirst, the need for security: a sense of confidence, freedom from fear and failure, the need for belonging and love, the need for respect), and then higher ones (cognitive needs: to know, to have certain abilities, to explore; aesthetic requirements: harmony, order and beauty; higher needs: implementation one‘s goals, abilities, self-development; self-actualization: the desire of an individual to have the fullest expression and development of existing positive qualities , capabilities and talents). That is why socialization is presented as a process of self-actualization «self-concept», self-actualization of one‘s potentialities and creative abilities as the process of overcoming the negative effects of the environment that interfere with his self-development and self-assertion. Here the subject is regarded as a self-standing and self-developing system through self-education. The article shows that self-actualized person has enough inner strength to act on basis of the own understanding of the situation, regardless of the opinions of others and their impact.
Keywords: self-actualization; socialization; adaptation; adaptation; self-development; self-education